The Effectiveness of Schema Therapy on Post-traumatic Growth and Self-Compassion in Women with Breast Cancer - Zavari, Nasrin; Sadati, Seyedeh Zahra; Hoseini, Morvarid Sadat; Zadhasan, Zohreh (Psychology of Woman Journal, 2025)
Objective: This study aimed to investigate the effectiveness of schema therapy in enhancing post-traumatic growth and self-compassion among women diagnosed with breast cancer.Methods and Materials: The study employed a randomized controlled trial design with two groups: an experimental group receiving schema therapy and a control group receiving no psychological intervention. Thirty women with breast cancer from Tehran were selected through purposive sampling and randomly assigned to each group (15 participants per group). The schema therapy intervention was conducted over ten weekly sessions, each lasting 60 minutes. Participants completed the Post-Traumatic Growth Inventory (PTGI) and the Self-Compassion Scale (SCS) at three time points: pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS version 27.Findings: The results showed a significant increase in post-traumatic growth and self-compassion in the experimental group compared to the control group across all stages. The experimental group’s mean post-traumatic growth scores improved from 48.73 (SD = 6.21) at pre-test to 67.85 (SD = 5.94) at post-test, while self-compassion scores increased from 62.19 (SD = 5.37) to 78.46 (SD = 5.08). Repeated measures ANOVA confirmed significant time and group interaction effects for both variables (Post-Traumatic Growth: F(2, 56) = 49.33, p < .001, η² = .78; Self-Compassion: F(2, 56) = 46.03, p < .001, η² = .77). Bonferroni post-hoc tests showed that improvements were statistically significant from pre-test to post-test and were sustained at follow-up.Conclusion: Schema therapy is an effective psychological intervention for promoting post-traumatic growth and enhancing self-compassion in women with breast cancer, with lasting effects observed up to five months after the intervention.